First report of fusarium wilt disease caused by Fusarium equiseti on grafted watermelon in Korea. - Han, You-Kyoung; Walftor, Dumin; Park, Mi-Jeong; Bae, Yeong-Seuk; Park, Jong-Han; Back, Chang-Gi (The American Phytopathological Society (APS), 2022)
In Korea, most grafted watermelons are a fusion of bottle gourd (Lagenaria siceraria) as a rootstock and watermelon (Citrullus lanatus) as a scionstock (Lee et al. 2010). Currently, we have collected several samples from grafted watermelon displaying symptoms of yellowing, withering, and wilting leaves. When the symptomatic stem was excised, browning vascular tissues were observed due to the colonization of a fungal pathogen. From the samples obtained, 25 fungal isolates were identified as species of Fusarium. Among 25 isolates, 18 were identified as F. oxysporum, four as F. solani, and three as F. equiseti. Initial assessment showed that one of the F. equiseti isolates (NIHHS 16-126) was highly virulent to rootstock. Interestingly, this is the first time F. equiseti has been identified as pathogenic to grafted watermelon. The NIHHS 16-126 isolate was collected from a watermelon cultivation field in Buyeo-gun (36.25951°N, 126.92044°E) county